2021
DOI: 10.1016/j.acap.2021.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Provider Focused Interventions to Improve Child and Adolescent Vaccination Rates

Abstract: Provider focused interventions can raise childhood and adolescent vaccination rates. Multi-component interventions are the most effective and are feasible with the help of electronic health records and quality improvement initiatives.'Audit and feedback' with respect to immunization is defined as providing information on measured vaccination rates to clinicians over a specified period of time so that they can assess and adjust their performance. Feedback on vaccination rates can be specific for individual clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 60 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…Many works highlighted the most effective interventions to increase vaccination rates were those directly targeted at the population who should get vaccinated 22 and those consisting of multiple strategies. 17 , 18 This review showed most intervention categories had mixed findings, showing both significant and non-significant results, especially if more outcomes were measured within one domain. No categories showed completely non-significant results across all outcomes, but very few had consistently significant positive results.…”
Section: Discussionmentioning
confidence: 97%
“…Many works highlighted the most effective interventions to increase vaccination rates were those directly targeted at the population who should get vaccinated 22 and those consisting of multiple strategies. 17 , 18 This review showed most intervention categories had mixed findings, showing both significant and non-significant results, especially if more outcomes were measured within one domain. No categories showed completely non-significant results across all outcomes, but very few had consistently significant positive results.…”
Section: Discussionmentioning
confidence: 97%
“…More than one approach is likely necessary to dramatically increase rates, as is needed for childhood and adolescent vaccines. 66 One example of combining multiple interventions is the AFIX-OB intervention. 67 This program was modeled after the CDCs AFIX QI program.…”
Section: Discussionmentioning
confidence: 99%